2009
DOI: 10.1504/ijfsnph.2009.026916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaemia on cognitive function in children

Abstract: Study was carried out on 150 school going children to study the relationship between iron deficiency anaemia and cognitive function. Children's were grouped into moderate anaemic, mild anaemic and nonanaemic. Haemoglobin levels were estimated by cyanmethaemoglobin method. Results indicate that 53.33% were mild anaemic, 12% moderate anaemic and 34.67% non-anaemic. Results significantly (p < 0.05) indicates that moderate anaemic children performed poor on attention, design fluency, verbal working memory N-back 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…In this study, all non-verbal items of Stanford Binet fifth edition were non-significant between the control and ID groups, except Quantitative Reasoning and Working Memory items. The findings agreed with the results of Handa et al revealed that iron deficiency impairs the activities that involve verbal working memory [21] .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, all non-verbal items of Stanford Binet fifth edition were non-significant between the control and ID groups, except Quantitative Reasoning and Working Memory items. The findings agreed with the results of Handa et al revealed that iron deficiency impairs the activities that involve verbal working memory [21] .…”
Section: Discussionsupporting
confidence: 92%
“…Since ≥ 2 MD were more common in anaemic children than non-anaemic (79.9% vs 67.0%, p<0.001), therefore anemia can be taken as surrogate marker. Studies have also reported that children with decreased hemoglobin levels were poor performers in cognitive tests [ 15 ]. Previous literature shows that iron, folate and vitamin B12 deficiencies are found to be associated with low scorings in cognitive tests [ 39 42 ], which is similar to the findings of current study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in India, among school aged children and adolescents, reported widespread deficiency of micronutrients [7,[15][16][17][18][19]. However, no comprehensive multicentric study has been conducted in India to assess the impact of various crucial micronutrient deficiencies on general intelligence as well as specific cognitive functions in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The maturation and development of children’s central nervous systems and cognitive function are substantially influenced by nutrition [ 5 ]. Also, exposure to educational institution and social interactions play a crucial role in this regard.…”
Section: Introductionmentioning
confidence: 99%